Innovative Tax Collection Methods for Ukraine on the Path to A Green Economy - Iryna Novakovska; Nataliia Medynska; Dmytro Zaruba (Jurnal Perencanaan Wilayah dan Kota, 2026)
The article examines ways to improve the mechanism of tax collection in agricultural land use through the application of a correction coefficient based on soil nitrogen balance. The relevance of the study is driven by the need to introduce economic instruments that stimulate environmentally sound land use in line with the principles of the green economy and international climate commitments. The theoretical framework is grounded in the provisions of the Paris Agreement and European climate policy, which prioritize increasing greenhouse gas absorption in the land use sector. The study is based on the hypothesis that an increase in humus reserves, accompanied by reduced greenhouse gas emissions, should justify a lower tax burden for land users, thereby creating economic incentives for restoring agricultural land potential. The proposed approach uses the ratio between nitrogen removal with harvest and its return to the soil as the key parameter for calculating the correction coefficient. A value below one indicates soil restoration and supports reduced tax assessments, while a value above one reflects degradation and justifies higher tax liabilities. The methodology is enhanced by incorporating UN IPCC (2019) correction factors that account for land use practices, soil management and nutrient return intensity. Practical application in the Odessa region demonstrates the flexibility and effectiveness of the mechanism, which can be integrated into tax assessment, land valuation and regional development systems to promote sustainable land use.